Pattern of joint involvement in post-dysenteric reactive arthritis - a preliminary report - Wijesiriwardena, B.C.; Jayasinghe, K.S.A.; De Mel, W.C.P.; Sheriff, M.H.R.; Dharmadasa, K. (My University, 1984)
The aim of the study was to determine the pattern of joint involvement in post-dysenteric arthritis as seen in Sri Lanka. Patients presenting with joint symptoms, following a dysenteric illness. Occurring within 6 weeks were included in the study. In this prospective study 35 consecutive patients with post-dysenteric arthritis admitted to general Hospital Colombo between July 1982 and July 1983, were studied. During this period there was an epidemic of bacillary dysentery and the responsible organism was Shigella dysenteriae Type 1. The time interval between commencement of diarrhoeal illeness and onset of joint symptoms varied between 1day 5 weeks, the average being 10 days. The most frequently involved joints at the onset were the knee (In 30%) and the ankle joints (In 31%). During the course of the illness the predominantly affected joint was knee joint (In 88%), the ankle being the 2nd commonest (in 50%). The number of joints affected during the course of the illness was less than 5 in the majority (87%). In 48% (36) of the joints affected, the arthritis was severe with warm tender joints and in 36% (27) there was an accompanying effusion. The time interval between involvement of two consecutive joints varied between 1 day and 2 weeks, the average being 2-5 days.